AN ANALYSIS OF SPEECH ACT USED IN DORA AND THE LOST CITY OF GOLD MOVIE - Yunafiun Nayyiroh; Dholiful Hadi; Mansur; Dyah Kurniawati (Pro-ELLitera, 2025)
This study aims to find out the pragmatics speech act classification 1) What are the types of illocutionary act 2) What is the most dominant types of illocutionary act performed by the main character in the movie titled Dora and the Lost City of Gold. Here, this research used a qualitative descriptive method to analyze the data provide. From the data , the researcher discovered 76 utterances which is spoken by the main character that contain four out five speech act s by Searle’s theory (1969). In this study, the result shows as expressive holds the top among all speech acts types with the 28 data found (37%). The other speech act show Directive as the second position with 27 data (35%), the third is Representative with 16 data (21%), fourth is Commissive 5 (7%) data, and the last position is Declarative with 0 data (0%). Keywords: Pragmatics, Speech Act, Movie